Social impact bonds in light of maqasid al-shari‘ah and maslahah - Syed Azman, Syed Marwan Mujahid (Islami Bank Training and Research Academy, 2015)
This paper looks into the concept of Social Impact Bond (SIB) and its underlying principles with regards to the Islamic values embodied within the components of maqasid al-Shari‘ah and maslahah. Using various literatures related to the study of maqasid al-Shari’ah and maslahah, as well as researches related to SIB, the paper attempts to delineate the elements embedded within the theoretical practice of SIB and look at them from an Islamic perspective. The paper explicates that the SIB is a model that epitomises the ethical and moral framework of Islamic law, as the elements of SIB are congruent with the concepts within maqasid al-Shari’ah and maslahah. The paper provides some insight of the concept of SIB as an alternative social financing model. As SIB embody the values that Islam teaches, this model should be looked into by organisations such as Islamic banks and Islamic financial institutions whose philosophical foundation is built upon the principles of maqasid al-Shari’ah and maslahah.